Ácido láurico apresenta efeitos antidepressivos em modelos modelos preditivos de depressão - Ribeiro, Maria Lorrana Assêncio (2024)
Depression comprises a disabling mental disorder with a high prevalence in the world population. Although there are several treatments for depression, medications cause many side effects. Thus, the study of new drugs of plant origin has been the target of several scientific researches. Lauric Acid (LA), one of the major components of coconut oil, comprises a saturated fatty acid that is easily metabolized by the body and has antioxidant and antiinflammatory effects. In this study we evaluated the activity of Lauric Acid in predictive models of depression such as forced swimming and tail suspension. For this, male Swiss mice were treated for 14 days with lauric acid at doses of 10, 20 and 40 mg/kg, fluoxetine 20 mg/kg or saline. The behavioral evaluation showed that lauric acid had an antidepressant-like effect in the forced swimming and tail suspension test and improved the animals' explorator y and cognitive capacity. In the neurochemical analysis, it reduced malondialdehyde levels in all doses administered and recovered glutathione levels at a dose of 40 mg/kg, showing antioxidant and modulating activity of the endogenous antioxidant system. It is concluded that the present work provided pre-clinical evidence of lauric acid as a new therapeutic approach to be used in the treatment of neuropsychiatric diseases such as depression